2008
DOI: 10.1364/oe.16.010405
|View full text |Cite
|
Sign up to set email alerts
|

Nano-FROG: Frequency resolved optical gating by a nanometric object

Abstract: Abstract:We present a technique to characterize ultrashort pulses at the focal plane of a high numerical aperture objective with unprecedented spatial resolution, by performing a FROG measurement with a single nanocrystal as nonlinear medium. This approach can be extended to develop novel phase-sensitive techniques in laser scanning microscopy, probing the microscopic environment by monitoring phase and amplitude distortions of femtosecond laser pulses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 30 publications
0
47
0
Order By: Relevance
“…objective with sub-diffraction limited resolution was presented by Extermann et al [56]. In that case, an interferometric set-up was used to delay in time two replicas of a beam collinearly focused by a 1.3 N.A.…”
Section: Ultrashort Pulses Characterizationmentioning
confidence: 99%
“…objective with sub-diffraction limited resolution was presented by Extermann et al [56]. In that case, an interferometric set-up was used to delay in time two replicas of a beam collinearly focused by a 1.3 N.A.…”
Section: Ultrashort Pulses Characterizationmentioning
confidence: 99%
“…These advantages make NPs more cost effective and easier to handle than their bulk crystal counterpart. The SH emission from single nonlinear NPs [13][14][15][16][17][18] and nanotips 19 interacting with ultrafast pulses has recently been detected and studied. Using frequency-resolved optical gating, Extremann et al…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the broadband excitation corresponding to a 10-fs pulse offers the possibility of spectral manipulation for coherent control (Warren et al, 1993;Weiner, 2000) of two-photon absorption and non-resonant second harmonic generation (Broers et al, 1992;Meshulach & Silberberg, 1998;Wnuk & Radzewicz, 2007). While it has been recently shown that a SHG-active nanoparticle of a size about a few hundreds of nanometers can be used for pulse detection in a nanoscopic version of the FROG technique (Extermann et al, 2008), the effects of manipulation of the excitation beam on SHG emission, i.e.,decreasing the time duration of a precompensated pulse as well as structuring its broadband spectrum, have not yet been investigated at the single nanoparticle level with a size well below the wavelength of light. Moreover in this size range phase matching conditions are automatically fulfilled, improving the coherent emission.…”
Section: Coherent Nonlinear Emission From a Single Ktp Nanoparticle Wmentioning
confidence: 99%